Student Satisfaction With Teaching Performance, Academic Administration Services, And Learning Facilities - Suryanto, Ahmad Eko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This journal aims to evaluate student satisfaction with the teaching performance of lecturers, academic administration services, and teaching facilities/infrastructure in a university. The method used was a survey with a questionnaire distributed to students at the university. The survey results showed that the majority of students were satisfied with the teaching performance of lecturers, academic administration services, and teaching facilities/infrastructure. However, there are still a small number of students who feel dissatisfied, especially with the teaching facilities/infrastructure. In terms of the teaching performance of lecturers, the majority of students feel satisfied and very satisfied with the willingness or concern of lecturers in helping them. While in the aspect of academic administration services, the majority of students feel satisfied and very satisfied with the willingness or concern of administrative staff in helping them. However, in the aspect of teaching facilities/infrastructure, there are still a small number of students who feel dissatisfied with the sufficiency, quality, and accessibility of the facilities and infrastructure available. From these survey results, it can be concluded that although the majority of students feel satisfied with the teaching performance of lecturers, academic administration services, and teaching facilities/infrastructure, there is still a need to improve the quality of teaching facilities/infrastructure to maximize student satisfaction.